Non Destructive Inner Quality Prediction In Intact Mango With Near Infrared Reflectance Spectroscopy - Agus A Munawar; I Wayan Budiastra (Jurnal Keteknikan Pertanian, 2009)
Two major parameters which determine inner quality and the taste of mango, total soluble solids (TSS) and firmness, are still determined destructively. To evaluate the feasibility of near infrared reflectance spectroscopy (NIRS) technique in determining total soluble solids (TSS) contents and firmness in intact mango, diffuse reflectance (R) spectra were measured in the spectral range from 900 to 1400 nm. Calibration models using R and log (1/R) were established by stepwise multiple linear regression with k-fold leave oneout (LOO) cross validation. The correlation coefficients (r) of calibrations ranged from 0.89 to 0.96 with SEC values 0.46 to 1.08. Both TSS and firmness were predicted accurately using log (1/R) spectra.Keywords: mango, NIRS, firmness, TSS, non-destructiveDiterima: 8 Juni 2008; Disetujui: 31 Januari 2009